2005
DOI: 10.1902/jop.2005.76.10.1667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Human Bone Morphogenetic Protein‐2, ‐4, and ‐7 on Bone Formation in Rat Calvarial Defects

Abstract: Within the rhBMP types used, rhBMP concentration, and the observation interval, there appears to be no specific differences in bone regenerative potential. All rhBMPs used in this study may be considered effective factors for inducing bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 36 publications
3
44
0
3
Order By: Relevance
“…In most cases of bone treated by 30 µg rhBMP-2, the dose was too high, causing new bone area to overgrow. The minimum effective dose of rhBMP-2 in rat femur bone healing was difficult to predict because the amounts of rhBMP-2 used in rat studies with collagen as a carrier have ranged from 0.5 to 200 µg [2,10,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases of bone treated by 30 µg rhBMP-2, the dose was too high, causing new bone area to overgrow. The minimum effective dose of rhBMP-2 in rat femur bone healing was difficult to predict because the amounts of rhBMP-2 used in rat studies with collagen as a carrier have ranged from 0.5 to 200 µg [2,10,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The ideal scaffold materials should be resorbed over time to allow cell infiltration and extracellular matrix deposition for new bone formation, while maintaining its osteoconductive properties until they are no longer required [17][18][19] . So far, ACS has been extensively used as an appropriate carrier for BMPs in bone reconstructive surgery 2,3,20,21) . Conversely, Bergeron et al recently reported that the injection of a chitosan-based BMP-9 gel induced ectopic bone formation, whereas collagen-based BMP-9 gel injection failed to promote ectopic ossification in mouse quadriceps 22) .…”
Section: Introductionmentioning
confidence: 99%
“…The number of materials used as carriers to accomplish delivery of BMPs at the site of implantation is huge and includes mineralized scaffolds [e.g. [8][9][10][11][12], metals [13], polymers [14,15], silk [16,17] and collagen [18][19][20][21]. However, most of these materials are unable to maintain a defined shape after implantation because they are either too soft or difficult to stabilize.…”
Section: Introductionmentioning
confidence: 99%